Impact of Appointment-Based Medication Synchronization on Proportion of Days Covered for Chronic Medications - Nancy Dao; Sun Lee; Micah Hata; Lord Sarino (MDPI AG, 2018)
Appointment-based medication synchronization (ABMS) programs have been associated with increased adherence and persistence to chronic medications. Adherence to statin therapy, angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), and non-insulin antidiabetic medications (NIDM) are used to determine a health plan’s Centers for Medicare and Medicaid Services (CMS) Star Rating under a pay-for-performance model. The objective of this study was to evaluate the impact of implementing an ABMS program on overall pharmacy adherence measures for statins, ACEI/ARBs, and NIDM, as presented through the Electronic Quality Improvement Platform for Plans and Pharmacies (EQuIPP©) platform. This retrospective, pre-post ABMS program study evaluated EQuIPP© generated adherence performance measures, represented as proportion of days covered (PDC), 6-months before and 6- and 12-months after the ABMS service for statin therapy, ACEIs/ARBs, and NIDM. All adherence measures showed statistically significant improvement in PDC percentage post ABMS implementation, except for NIDM percentage in 6-months post-ABMS service. This study shows that a comprehensive medication synchronization program can enhance adherence measures that are important to health plans to increase CMS Star Rating under a pay-for-performance model.